EDUKASI 3 M (MEMAKAI MASKER, MENCUCI TANGAN, MENJAGA JARAK) DAN BERITA HOAX KEPADA ANAK-ANAK RW 010 KELURAHAN CAWANG, JAKARTA TIMUR - IMELDA MASNI JUNIATY SIANIPAR (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2021)
Abstract The Corona Virus, commonly known as COVID-19, is haunting the world. It began in China and spread throughout the world. Despite the fact that it has resulted in several deaths, many people, especially those in Indonesia, are still unconcerned about the dangers of the Corona virus. The community service program carried out by lecturers and students from Departement of International Relations and Departement of Communication, Faculty of Social and Political Science, Universitas Kristen Indonesia aims to raise awareness of clean and healthy life behavior (PHBS) among children in RW 10, Cawang sub-district, East Jakarta. 3M education attempts to raise children's awareness of the importance of wearing masks in public places, washing their hands thoroughly with soap, and keeping their distance, while hoax news education attempts to remind children to be wary of the news they consume from television and the internet. The method of presentation and competition was employed. This community services program (PKM) takes place both on-site and online. A total of 60 children aged 6 to 11 attended this event. This article results children in RW 10, Cawang sub-district, East Jakarta are becoming more aware of the importance of wearing masks, washing their hands thoroughly, keeping their distance, and recognizing hoax news. Furthermore, competitions such as painting on masks, drawing, coloring, and making videos “me and Corona” have succeeded in increasing the children's enthusiasm to be active after undergoing distance education beginning in March 2020. Keywords: Covid-19 virus, 3M, hoax, children in Rw 10, Cawang subdistrict, East Jakarta